1988
DOI: 10.1093/schbul/14.3.471
|View full text |Cite
|
Sign up to set email alerts
|

Workshop on Schizophrenia, PET, and Dopamine D2 Receptors in the Human Neostriatum

Abstract: Recently, two research groups published numbers for D2 receptor sites in the neostriatum of drug-naive schizophrenic patients, obtained in vivo by positron emission tomography (PET). One study appeared to confirm the increase of D2 receptor numbers, while the other study did not. A workshop was convened in Montreal to examine the reasons for the discrepancy between the results obtained by the two groups. The workshop considered patient populations, PET instrumentation and scanning methods, pharmacology, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 35 publications
1
43
0
1
Order By: Relevance
“…37 In one study using [ 11 C]-methylspiperone, a significant elevation in D 2/3 receptor densities was observed in patients with longer duration of illness; 6 whereas in another study involving patients with shorter duration of illness, no significant difference was found, as determined by [ 11 C]-Raclopride. 38 Some of the patients with schizophrenia included in the latter study did not meet the DSM-III severity criteria for the disease during the study period, and most had a relatively short duration of illness.…”
Section: Discussionmentioning
confidence: 99%
“…37 In one study using [ 11 C]-methylspiperone, a significant elevation in D 2/3 receptor densities was observed in patients with longer duration of illness; 6 whereas in another study involving patients with shorter duration of illness, no significant difference was found, as determined by [ 11 C]-Raclopride. 38 Some of the patients with schizophrenia included in the latter study did not meet the DSM-III severity criteria for the disease during the study period, and most had a relatively short duration of illness.…”
Section: Discussionmentioning
confidence: 99%
“…These studies yielded controversial results with respect to whether medication-naive schizophrenic patients showed an elevated number of dopamine D 2 receptors in the striatum, interpreted initially as being consistent with the hypothesized dopaminergic hyperactivity. These findings have been the subject of continuous debate concerning differences in method and subject characteristics across studies (4). One of the most important issues raised in comparing the data across studies is that the discrepancies observed may be attributable to differences in the binding affinities of the two radiotracers for the D 2 receptor, and therefore the sensitivity of ligand binding to alterations in endogenous dopamine concentrations would differ as well (5).…”
mentioning
confidence: 99%
“…For example, the first application of these techniques to neuropsychiatric disease addressed one important component of the dopamine hypothesis of schizophrenia (1,2). However, the results were controversial and have been the subject of continued debate with respect to differences in methodology and subject characteristics (3,4). Therefore, the need to further study mechanisms that regulate synaptic dopamine activity is supported not only by the evidence that schizophrenic patients may or may not show significant changes in dopamine receptor number (Bmax) from normal controls but by the fact that the degree of striatal D2 receptor occupancy is not indicative of response to neuroleptic treatment (5,6).…”
mentioning
confidence: 99%